O habitus professoral: o objeto dos estudos sobre o ato de ensinar na sala de aula - Silva, Marilda Da [UNESP] (ANPEd - Associação Nacional de Pós-Graduação e Pesquisa em Educação, 2005)
This article is an attempt to define the proposed concept of professorial habitus, a process that has been under way since the end of the 1980's. However, the attempt to produce a more stable theoretical structure for the concept took until the end of the 1990's. Professorial habitus is the theoretical-methodological way of building a resource capable of explaining teachers' behaviour and, above all, of re-addressing the object of study directed at the act of teaching in the classroom. The place of theory and practice in the formation and activity of teachers was investigated simultaneously and, at the same time, served as a tool for formulating the concept in question. The ideas of Pierre Bourdieu and Edward Palmer Thompson (habitus and experience) constituted the core of the theoretical framework of this investigation.

Este artigo objetiva definir o conceito intitulado habitus professoral, esforço que vem sendo feito desde o fim da década dos anos de 1980, mas que somente no final dos anos de 1990 conseguiu alcançar uma estrutura teórica mais estável. Habitus professoral é o caminho teórico-metodológico da construção de um recurso explicativo dos comportamentos de professores, sobretudo, do re-endereçamento do objeto de estudo do ato de ensinar na sala de aula. Os lugares da teoria e da prática na formação e atuação docentes foram simultaneamente analisados, servindo de ferramentas para a formulação do conceito em questão. As idéias de Pierre Bourdieu e Edward Palmer Thompson (habitus e experiência) constituíram o núcleo do referencial teórico desta investigação.
Professorial habitus: the object of studies about the act of teaching in the classroom
Keywords: professorial habitus; classroom teaching; habitus professoral; ensino em sala de aula